THE IMPACT OF RISK MANAGEMENT ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN UGANDA: A CASE OF HOUSING FINANCE BANK MUKONO BRANCH - Suzi Awut Marial (My University, 2024)
ABSTRACT The purpose of the study was to ascertain the impact of risk management on the fianacial performance of commercial banks in mukono Uganda.. Following the foregoing, the researcher put out the following fundamental research questions: How much does the financial performance of medium-sized businesses in Mukono Municipality, Uganda, suffer from the risk management? How much does operational risk management impact the financial performance of Uganda's Mukono Municipality's medium-sized businesses? What impact does credit risk management have on medium-sized businesses' financial performance in Uganda's Mukono Municipality? Although it only managed to obtain 97% of the responses from 34 staff members, the case study of Housing finance bank had 35 staff members as its target audience (management and employees). In the research, data collection was done through the use of structured questionnaires and conducting interviews. To collect the primary data, a structured questionnaire was employed in collecting the data. The analysis was facilitated by a computer software program known as Statistical Package for Social Sciences. In analyzing data, quantitative data was analyzed and output presented by using descriptive statistic percentages. After qualitative data analysis, the results were narrated. Every responder expressed agreement that monitoring an organization's financial performance is beneficial, and that credit risk management is an efficient and effective way to minimise financial losses. Many of the interviewees denied that their organisation had liquidity risk management. The study comes to the conclusion that medium-sized businesses are at financial danger when liquidity risk management is lacking. Thus, this study comes to the conclusion that risk management and the financial performance of medium-sized businesses in Uganda's Mukono Municipality are significantly